PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN AKIDAH AKHLAK KELAS VII MTs AL–QUDSIYAH KLOTOK PLUMPANG TUBAN - Afidatus Shoimatut Tajdidiyah; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (VICRATINA, 2021)
The study entitled application of mind mapping methods to improve student learning outcomes in akhlak class VII MTs Al-Qudsiyah Klotok Plumpang Tuban. Discussed three problem formulations, namely the ability of teachers to manage learning with the mind mapping method, improving student learning outcomes by applying the mind mapping method in class VII MTs Al-Qudsiyah Klotok Plumpang Tuban, advantages and disadvantages of the mind mapping method. The method used in this study is a classroom action research method with this type of participant research. Data collection techniques using observation, test questions, and documentation. The results showed that. First, improving the ability of teachers in managing learning in each cycle. In the first cycle the percentage is 80% (enough), and in the second cycle 94% (very good). Second, the results of the first cycle of learning tests there are 17 students (51%) completed, and 16 students (48%) have not completed, cycle II there are 28 students (84%) completed, and 5 students (15%) have not completed, the category of learning completeness students in this learning is if the value reaches 75%. Third, the advantages of the mind mapping method are: the technique of summarizing notes is flexible, can focus attention, improve student understanding, and is fun. The drawback is that only active students are involved and the process does not fully occur. It was concluded that the mind mapping method could improve the learning outcomes of class VII-A MTs Al Qudsiyah Klotok Plumpang Tuban. Kata Kunci: learning methods, Mind  Mapping,  Improve student learning outcomes.